Recent advances in natural anti‐HIV triterpenoids and analogs - Wu, Hai‐Feng; Morris‐Natschke, Susan L.; Xu, Xu‐Dong; Yang, Mei‐Hua; Cheng, Yung‐Yi; Yu, Shi‐Shan; Lee, Kuo‐Hsiung (Medicinal research reviews, 2020)
The human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) epidemic is one of the world's most serious health challenges. Although combination antiretroviral therapy provides effective viral suppression, current medicines used against HIV cannot completely eradicate the infectious disease and often have associated toxicities and severe side effects in addition to causing drug resistance. Therefore, the continued development of new antiviral agents with diverse structures and novel mechanisms of action remains a vital need for the management of HIV/AIDS. Natural products are an important source of drug discovery, and certain triterpenes and their analogs have demonstrated potential as pharmaceutical precursors for the treatment of HIV. Over the past decade, natural triterpenoids and analogs have been extensively studied to find new anti‐HIV drugs. This review discusses the anti‐HIV triterpenoids and analogs reported during the period of 2009–2019. The article includes not only a comprehensive review of the recent anti‐HIV agent development from the perspective of medicinal chemistry, but also discusses structure–activity relationship analyses of the described triterpenoids.